TECHNOSOL TANAH MASA DEPAN - Dian Pratama Putra Suwarno (AGROISTA : Jurnal Agroteknologi, 2018)
Land as a medium of all living things that live above or below, humans themselves are very dependent on the land because without the land there will be no plants and food products that are useful for human life. Environmental damage is increasingly occurring today, making the elimination of the use of land that had been for a living being to be disturbed. Techosol is a land where there is a very large human influence, former land of buildings, building debris, ex-mining and land that needs to be reclaimed can also be categorized as Technosol soil. The function of this land in the future is crucial because it can be useful not only as a means of reclamation, but also as a living place or even living as a profitable agricultural land. Keywords: Technosol, soil reclamation, environmental,microorganism.